2022
DOI: 10.1002/hsr2.589
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation versus magnetic resonance imaging findings in patients with radicular arm pain—A pragmatic study

Abstract: Objectives: Cervical nerve root compression can lead to radiculopathy in the arm. Some studies have reported low accuracy in determining the responsible nerve root in both cervical and lumbar regions. This prospective, observational, pragmatic study aimed to determine the accuracy of the clinical evaluation relative to magnetic resonance imaging (MRI) findings in patients with arm radiculopathy.Methods: Patients with neck pain and neck-related arm pain referred to a spine unit underwent a standard clinical neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…As a result, similar to lumbar radiculopathy, the main criteria we recommended for RCTs assessing conservative interventions are based on history and clinical examination findings 110. Researchers who use imaging for further confirmation need to correlate findings to participants clinical presentation as in isolation, imaging cannot reliably be used due to its high false-positive rate 45,64,92,102,111. If authors use imaging to help diagnose CR, we urge them to identify and report the symptom etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, similar to lumbar radiculopathy, the main criteria we recommended for RCTs assessing conservative interventions are based on history and clinical examination findings 110. Researchers who use imaging for further confirmation need to correlate findings to participants clinical presentation as in isolation, imaging cannot reliably be used due to its high false-positive rate 45,64,92,102,111. If authors use imaging to help diagnose CR, we urge them to identify and report the symptom etiology.…”
Section: Discussionmentioning
confidence: 99%
“…110 Researchers who use imaging for further confirmation need to correlate findings to participants clinical presentation as in isolation, imaging cannot reliably be used due to its high false-positive rate. 45,64,92,102,111 If authors use imaging to help diagnose CR, we urge them to identify and report the symptom etiology. As our review found, the body of literature surrounding the impact of different aetiologies on the clinical course of CR is lacking and more information is needed.…”
Section: Proposed Recommended Inclusion Criteria and Justificationmentioning
confidence: 99%
“…In addition, since it takes many years for degeneration to extend to multiple intervertebral levels or distal to the intervertebral foramen, irreversible damage to the nerve roots may occur due to chronic nerve root compression. Furthermore, since the imaging evaluation of the intervertebral foramen for cervical radiculopathy is sometimes mismatched with physical findings, 6,14 the imaging of multilevel intervertebral stenosis for a definitive diagnosis of the responsible levels may be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Moreover, physical examination findings often mismatch or overlap with the classical dermatome of each nerve root, 5 resulting in a low correlation between subjective symptoms and objective imaging findings. 6 When there is no diagnostic confidence regarding the site of the responsible lesion, electromyography (EMG) or selective nerve root block (SNRB) is sometimes used. However, these invasive techniques do not always provide an accurate diagnosis.…”
mentioning
confidence: 99%
“…A cervical MRI is a definitive examination for evaluating patients with a history of cervical radiculopathy or myelopathy symptoms [25]. In cases of radiculopathy, the results of the MRI examination should be related to the physical examination, considering that protrusion or extrusion of the disc can reach > 30% of patients [26].…”
Section: Laboratory Tests and Imagingmentioning
confidence: 99%